Legal Protection Guarantee on the Effect of Home Ownership Credit Consumers the Deed Which Was Made by a Notary in Pekanbaru - Dian Dini, Kirana (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to determine and analyze the role of Notaries in ensuring legal protection for Home Ownership Credit consumers in Pekanbaru and to determine and analyze the legal efforts made by consumers in the implementation of Home Ownership Credit in Pekanbaru. The research approach method used in this thesis is an empirical legal research method. The specifications of this study use descriptive analysis. The types of data used in this study are primary data which include the 1945 Constitution; Law No. 2 of 2014; Mortgage Law; Civil Code; Law No. 8 of 1999; Basic Agrarian Law; Law No. 1 of 2011; as well as secondary data containing books and other supporting documents. Research data collection using interview techniques and document studies or library materials. The data analysis method used in analyzing the data is qualitative analysis. The results of the study indicate that Notaries play a crucial role in securing the fulfillment of the legal requirements for subsidized home ownership deeds. In this study, it can be concluded that the role of a notary is related to the legalized subsidized home credit agreement deed, which must fulfill all applicable provisions and regulations so that its legal validity and completeness are met. Legal protection for third parties in the implementation of credit for objects of mortgage guarantee is regulated in Article 1 paragraph (1) No. 8 of 1999 concerning the Consumer Protection Law.